High glucose induces O‐GlcNAc glycosylation of the vitamin D receptor (VDR) in THP1 cells and in human macrophages derived from monocytes. (9th August 2017) - Hernández‐Sánchez, Fernando; Guzmán‐Beltrán, Silvia; Herrera, María Teresa; Gonzalez, Yolanda; Salgado, Manuel; Fabian, Guadalupe; Torres, Martha
Abstract: Chronic hyperglycemia increases the carbon flux through the hexosamine pathway, allowing the accumulation of UDP‐GlcNAc. UDP‐GlcNAc is the sugar donor for the enzyme‐mediated protein glycosylation event known as OGlcNAcylation. This posttranslational modification targets several transcription factors implicated in glucose toxicity, insulin resistance, and diabetes. Vitamin D plays an important role in glucose homeostasis and insulin secretion through transcriptional mechanisms mediated by its receptor (VDR). Vitamin D deficiency has been associated with higher susceptibility to bacterial diseases in diabetic patients. However, it has not been explored whether VDR is subject to OGlcNAcylation or whether high glucose affects its transcriptional or biological activities. The aim of this study was to evaluate the effect of hyperglycemia on VDR OGlcNAcylation and its effects on vitamin D‐mediated transcription. We predicted potential OGlcNAcylation sites using free software. Our results showed that hyperglycemia (30 mM) induces the OGlcNAcylation of VDR in THP1 cells and in human macrophages derived from monocytes (MDM). This condition did not hamper the vitamin D‐dependent activation of LL‐37 gene expression, and even did not impair the macrophage bactericidal activity. Our study provides new insight into vitamin D receptor posttranslational modification that may have relevance on the physiological responses of long‐term hyperglycemia.